Determining The Priorities for Small and Medium Enterprise Development in Candipuro District Using the Analytical Hierarchy Process (AHP) Method - Yuli Syafitri; Reni Astika; Irwandi; Deddy Sulaimawan (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2025)
This study aims to determine the priority of SME development strategies in Candipuro Subdistrict, South Lampung, by applying the Analytical Hierarchy Process (AHP) method as a multi-criteria decision-making approach. This study fills the gap in previous studies, which generally only assessed single factors and did not comprehensively integrate capital, marketing, human resources, and technology at the subdistrict level. Data were obtained through expert assessment and analysed using a pairwise comparison matrix. The results showed that capital was the most important criterion in SME development, followed by marketing, human resources, and technology. The strategy of increasing access to capital is considered the top priority alternative, followed by strengthening digital marketing and increasing human resource capacity. All calculations meet the consistency ratio value (CR < 0.1), so the results are considered valid. This emphasises the need for policies to strengthen access to funding and digitalisation of MSMEs as the main focus in local economic development.